The impact of long-term moderate and heavy alcohol consumption on incident atherosclerosis among persons living with HIV. (1st December 2017) - Kelso-Chichetto, N.E.; Plankey, M.; Sheps, D.S.; Abraham, A.G.; Chen, X.; Shoptaw, S.; Kaplan, R.C.; Post, W.S.; Cook, R.L.
Highlights: Longitudinal study of alcohol use and incident atherosclerosis among HIV+ persons. Heavy alcohol use was not significantly associated with incident atherosclerosis. Moderate alcohol use was associated with lower odds for incident disease in men. Abstract: Background: Level of alcohol consumption is associated with differential risk of atherosclerosis, but little research has investigated this association among HIV+ persons. We evaluated the association between long-term alcohol use and incident atherosclerosis among HIV+ persons. Methods: We utilized data from HIV+ participants of the Women's Interagency HIV Study (n = 483) and the Multicenter AIDS Cohort Study (n = 305) without history of cardiovascular disease. Atherosclerosis was assessed two times by B-mode carotid artery ultrasound imaging from 2004 to 2013. Presence of plaque was defined as focal carotid intima-media thickness over 1.5 mm. Those with no plaque at baseline and plaque at follow-up were considered incident cases of atherosclerosis. Group-based trajectory models were used to categorize participants into 10-year drinking patterns representing heavy, moderate, or abstinent-low. Multivariable logistic regressions were conducted to assess the association of long-term moderate and heavy use on atherosclerosis, compared to abstinent-low. Results: Heavy alcohol consumption was not statistically significantly associated with risk for incident atherosclerosis in women (AOR 1.10, CI 0.40–3.02) or men (AOR 1.31, CI 0.43–4.00), compared to abstinence-low. Moderate consumption was associated with 54% lower odds for incident disease in men (AOR 0.46, CI 0.21–1.00), but not in women (AOR 1.08, CI 0.58–2.00). In cohort-combined analyses, alcohol consumption was not statistically significantly association with incident atherosclerosis (moderate AOR 0.78, CI 0.48–1.27; heavy AOR 1.33, CI 0.66–2.69). Conclusion: Moderate alcohol consumption was associated with a significant protective effect on incident atherosclerosis in men only. No other levels of alcohol consumption significantly predicted atherosclerosis in men and women compared to abstinent-low.